Respons N-Total, P-Potensial dan K-Potensial dan Hasil Jagung Manis (Zea mays saccharata Sturt) akibat Pemberian Pemupukan Pupuk Organik Remah dan NPK pada Tanah Inceptisol - Sara, Dirga Sapta; Sofyan, Emma Trinurani; Joy, Benny (Soilrens, 2024)
Sweet corn is an agricultural commodity that has increasing market demand and high economic value. To achieve optimal production results, proper fertilization is very important, especially on Inceptisol soils that have low to medium fertility. This study aimed to evaluate the combination of crumb organic fertilizer and NPK fertilizer on soil N-total, P-potential, and K-potential as well as sweet corn crop yield. The experiment was conducted from September to December 2023 at the Experimental Field, Padjadjaran University, using Inceptisol soil, sweet corn seeds, crumb organic fertilizer, and NPK fertilizer (15-15-15). Randomized Group Design, six treatments including control, recommended dose of NPK fertilizer, and combination of crumb organic fertilizer with NPK, repeated 4 times. Analysis in the maximum vegetative phase at 55 HST with testing parameters including soil N-total (Kjeldahl method), P-potential (Bray method), K-potential (ammonium acetate method). The results showed that the combination of ¾ NPK and 1 ½ crumb organic fertilizer was effective in increasing soil N-total, P and K-potential and sweet corn yield.